Bioreactor septic tank for on-site wastewater treatment: Floating constructed wetland integration. Issue 4 (August 2021) - Saeed, Tanveer; Afrin, Rumana; Al-Muyeed, Abdullah; Miah, Md Jihad; Jahan, Hasin
Abstract: This study reports pollutant removal performance of two on-site wastewater treatment configurations: a field-scale bioreactor septic tank that received wastewater generated from the washrooms of an educational institute, and a combined pilot-scale bioreactor septic tank, floating constructed wetland system dosed with municipal wastewater. Each bioreactor septic tank was divided into seven compartments: two settling chambers, two anaerobic baffle reactors (ABR), two stone media-packed biowalls, and an effluent collection chamber. Wastewater hydraulic retention time (HRT) in the field and pilot-scale bioreactor septic tanks were 24 and 72 h, respectively. Nitrogen (N), phosphorus (P), organic, and coliform removal percentage in the field-scale bioreactor septic tank were 56%, 76%, 84%, and 88%, respectively. The pilot-scale bioreactor septic tank achieved 93%, 100%, 99.6%, and 99.9% removal, respectively. Pollutant removal in different compartments of the bioreactor septic tanks was achieved through physical, chemical, and microbial degradation pathways. Greater HRT of wastewater in the pilot-scale bioreactor septic tank improved overall removal performance. The floating constructed wetland provided an additional treatment of the pilot-scale bioreactor septic tank effluent; the mean nitrogen and coliform removal percentage was 35% and 91%, respectively. The hanging root-zone (inside the water column) of the floating constructed wetland supported pollutant removal kinetics. This study demonstrates the potential application of the bioreactor septic tank for on-site wastewater treatment and integration of floating constructed wetland as a polishing stage. Graphical Abstract: ga1 Highlights: Bioreactor septic tanks achieved > 80% organic and > 60% nutrient removal. 72 h HRT improved pollutant removal in pilot-scale bioreactor septic tank. Floating constructed wetland polished the bioreactor septic tank effluent. Bioreactor septic tank-floating wetland are potential on-site treatment systems.